PEMBUATAN PUPUK BOKASHI BERBASIS KOTORAN SAPI - Dewi, Y.L.; Sinabang, M.K.; Kamlasi, Y.; Bere, E.K.; Citrawati, G.A.O. (Buletin Udayana Mengabdi, 2023)
Jenilu Village is one of the villages located in Kakuluk Mesak District, Belu Regency, East Nusa Tenggara. Jenilu Village has a women's farmer called KWT Wero. This farmers are active in agricultural activities such as planting horticulture. In addition, the KWT Wero Farmers have a cattle farm with a semi-intensive rearing system. Cattle farming by the community produces waste in the form of livestock manure. This waste is a lot and has not been utilized by the community. The purpose of this community service is to increase the knowledge and skills of the community in the use of cow dung as an ingredient for making bokashi fertilizer. The approach taken is a participatory approach with a series of activities that include counseling, training, demonstration/practice, and mentoring. The result of community service activities in Jenilu Village is bokashi fertilizer made by the community. The results of the production of bokashi fertilizer are used by the KWT Wero Farmers as an alternative to the use of inorganic fertilizers in increasing the production of horticultural crops. Keywords: Farmers, Agriculture, Livestock, Bokashi Fertilizer